Bridging the Gap amongst Visual, Auditory and Kinesthetic Learners in Biology through the Use of Dick and Carey Ibstructional Model - Adedoyin Adewale Adebanjo (University of Sofia, 2022)
Students with different learning styles are lumped in a classroom for instruction which resulted to poor academic achievement. To bridge the gap among them, Dick and Carey instructional model was employed. Therefore, the study examined the effect of Dick and Carey instructional model for bridging the gap amongst different categories of students learning style in biology. Pre-test, post-test, control group, switching replication quasi-experimental design, involving 2x3 factorial matrix was adopted. The sample consisted one hundred and two (102) SS 2 students offering biology in four purposively selected secondary schools, two schools each, from Odogbolu and Ijebu North Local Government Areas of Ogun State. Three hypotheses were formulated and tested at 0.05 level of significance. Three instruments were used to gather required data: Biology Achievement Test (r=0.85), Learning Styles Self-Assessment Test (r=0.64) and Dick and Carey Instructional Guide. Data were analyzed inferentially by Analysis of Covariance (ANCOVA). The results revealed that Dick and Carey instructional model had significant effect on achievement in biology. However, no significant main effect of students learning style was found on students achievement in biology. No significant 2-way interaction effect of students learning style was found in students achievement in biology. It is recommended that curriculum planners/policy makers should encourage biology teachers to use Dick and Carey instructional model in secondary schools in Nigeria in order to bridge the gap among visual, auditory and kinesthetic students during classroom instruction.